FUNCTION AND ROLE OF LIFE INSURANCE TO CUSTOMERS IN AJB BUMI PUTRA 1912 OPERATIONAL OFFICE ASKUM YOGYAKARTA - Nuwa, Elias; Lastari, SE., MM, Siwi; Darini, M.Si., Dra. Sri (Management, 2010)
Development which was held in Indonesia according to guidelines outlined by the society to realize a just, prosperous and prosperous, has been successfully realized. For the success of development is required close cooperation between the Government, on the one hand with the whole society on the other. But the success of such development has received little resistance by the monetary crisis that hit the world in early 1998. Monetary crisis in Indonesia has influenced the conditions become increasingly complex and multidimensional crisis worsening political, economic, social and cultural rights in Indonesia. Due to the monetary crisis that led to the joints of the Indonesian economy to collapse, all the real sector is not, many companies collapsed. However, on the other hand the more fertile area of insurance, because with the state of Indonesia is not yet stable economy supported reflux still cause a lot of shareholders capital / capital to insure its business in order to prevent bigger losses that arise suddenly and uncertain. An event resulting in loss of society can not be avoided on an individual basis by the parties concerned, but action must be held together by their collective interest, then the financial loss was borne together proportionally. Furthermore, insurance companies should arise understand the suffering of the people who intangible risk of financial loss, which can be reduced or avoided by the actions of those concerned together collectively bear the financial loss by means of "insurance", where insurance is a guarantee against self and possessions members community to reduce or avoid possible financial loss. Keywords : insurance, customers